Effect of an Eight-Week Preksha Meditation Programme on Symptom Severity and Quality of Life in Patients with Irritable Bowel Syndrome - Sarika Giria; Dr Pradyumna Singh Shekhawat (The Bioscan, 2025)
Background: Irritable Bowel Syndrome (IBS) is a prevalent functional gastrointestinal disorder strongly influenced by diet and psychological stress. The bidirectional mind–gut axis links emotional states with intestinal sensitivity, making symptom management complex. Conventional dietary interventions, such as the Low FODMAP (L-FODMAP) diet, alleviate physiological distress but often fail to address the underlying psychophysiological dysregulation. Preksha Meditation, a structured mindfulness-based practice rooted in Jain philosophy, focuses on breath awareness and self-observation, potentially enhancing autonomic regulation and reducing symptom severity. Objective: This study evaluated the combined effects of an eight-week Preksha Meditation programme and L-FODMAP dietary intervention on symptom severity and quality of life (QoL) in patients with IBS. Methods: A randomised controlled trial (RCT) was conducted with 90 IBS patients aged 18–65 years, assigned to one of three groups: (1) L-FODMAP diet, (2) L-FODMAP diet plus Preksha Meditation, and (3) control (standard IBS care). Pre- and post-intervention data were collected using the IBS-36 questionnaire measuring gastrointestinal, physical, emotional, social, and overall QoL domains. Data were analysed using paired t-tests and ANOVA with significance at p < .05. Results: Participants in the combined L-FODMAP + Preksha group exhibited the most significant reduction in gastrointestinal and psychological symptoms across all domains (p = .0001), demonstrating improvements in energy, mood, and overall QoL. Both the L-FODMAP-only and control groups showed lesser or negligible improvement. Conclusion: The integration of Preksha Meditation with dietary intervention offers a holistic, mind–body approach to IBS management. The results support incorporating meditative therapies alongside nutritional strategies for sustainable symptom reduction and improved well-being.